Kekerasan sebagai Kisah: Visualisasi Konflik Israel-Palestina dalam Novel Grafis Palestine dan Footnotes in Gaza - Saputra, Reno; Iqbal, Muhammad; Husni, Muhammad (NALAR, 2023)
This article examines the visualization of violence experienced by the Palestinian people against Israeli occupation in the Graphic Novel by Joe Sacco. This study is literature research using David Wasterfors' social theory of "Violence as a story". The primary data sources in this study are the graphic novels Palestine (2002) and Footnotes in Gaza (2010). This study uses a historical approach with the method of reading comic studies (science) to describe visually (images) and narratively based on the experiences of documentary studies (memorials) of the Palestinian people's struggle for independence. Through the "Violence as a Story" approach, this study found Joe Sacco's skill in telling the story of violence experienced by the Palestinian people against Israeli occupation from the beginning of the war in 1948 to the events that occurred in the graphic novel by combining images (visuals) and appropriate narratives as panels in the graphic novel. Readers are made to feel as if they are entering and feeling what the Palestinians feel.Keywords :